Nanosecond pulsed electric field induced changes in cell surface charge density. (September 2017) - Dutta, Diganta; Palmer, Xavier-Lewis; Asmar, Anthony; Stacey, Michael; Qian, Shizhi
Abstract: This study reports that the surface charge density changes in Jurkat cells with the application of single 60 nanosecond pulse electric fields, using atomic force microscopy. Using an atomic force microscope tip and Jurkat cells on silica in a 0.01 M KCl ionic concentration, we were able to measure the interfacial forces, while also predicting surface charge densities of both Jurkat cell and silica surfaces. The most important finding is that the pulsing conditions varyingly reduced the cells' surface charge density. This offers a novel way in which to examine cellular effects of pulsed electric fields that may lead to the identification of unique mechanical responses. Compared to a single low field strength NsPEF (15 kV/cm) application, exposure of Jurkat cells to a single high field strength NsPEF (60 kV/cm) resulted in a further reduction in charge density and major morphological changes. The structural, physical, and chemical properties of biological cells immensely influence their electrostatic force; we were able to investigate this through the use of atomic force microscopy by measuring the surface forces between the AFM's tip and the Jurkat cells under different pulsing conditions as well as the interfacial forces in ionic concentrations.